Kinerja Guru Pendidikan Agama Islam Bersertifikasi Di SMPN 2 Banyudono Kabupaten Boyolali Tahun Ajaran 2016/2017 - Apriliani, Iqqomah; , Drs. Zaenal Abidin M.Pd (2017)
In the law No.20 of 2003 on National Education System, it is argued that the meaning of teachers or educators are professionals in charge of planning and implementing the learning process, assessing learning outcomes, conducting mentoring and training, and conducting research and community service. To be able to perform its functions properly, then the teacher should improve its performance. Efforts to improve teacher performance are with teacher certification programs. Teacher certification is a competency test process for candidates or teachers who wish to gain recognition and improve their competence according to their chosen profession. This certification is a proof of recognition of the competence of teachers or prospective teachers who meet the standards to perform the work of the teaching profession on certain types and levels of education. Problems to be investigated in this study is how the performance of Islamic religious education teachers in SMP Negeri 2 Banyudono Boyolali District academic year 2016/2017. This study aims to determine the performance of certified Islamic education teachers. This research was conducted on Islamic religious teacher in SMP Negeri 2 Banyudono, Boyolali. The method in this research is kind of field research with qualitative approach, using qualitative descriptive analysis and inductive thinking pattern. Subjects in this study are head teachers and teachers of Islamic religious education. The data collection method used is documentation, observation and interview, while the method of data analysis is inductive analysis that is collecting data result of interview, observation and documentation. Then from the three data are analyzed and made conclusion. From the results of this study, it can be concluded that the Performance of Islamic Education Teachers Certified in SMP Negeri 2 Banyudono Boyolali District Academic Year 2016/2017. The performance of teachers after certification is near standard of performance. Teacher performance can be measured based on the competence that must be owned by Islamic religious education teacher that there are five competence: pedagogic, personality, social, professional, and religious competence.